Post-operative pulmonary complications after thoracic and upper abdominal procedures at referral hospitals in Amhara region, Ethiopia: a multi-center study - Admass, Biruk Adie; Ego, Birhanu Yilma; Tawye, Hailu Yimer; Ahmed, Seid Adem (Frontiers in Surgery, 2023)
Background: Thoraco-abdominal surgery cuts through muscle, disrupting the normal structure and function of the respiratory muscles, resulting in lower lung volumes and a higher risk of developing post-operative pulmonary complications (PPC). PPC remains an important cause of post-operative morbidity and mortality and impacts the long-term outcomes of patients after hospital discharge. This study was aimed at determining the incidence and factors associated with postoperative pulmonary complications among patients who underwent thoracic and upper abdominal surgery in the Amhara region of Ethiopia. Methods: A multi-center follow-up study was conducted from April 1, 2022, to June 30, 2022, at comprehensive specialized hospitals in Amhara regional state, northwest Ethiopia. 424 patients were consecutively included in this study, with a response rate of 100%. A chart review and patient interview were used to collect data. A logistic regression analysis was performed to assess the strength of the association of independent variables with postoperative pulmonary complications. The crude odds ratio (COR) and adjusted odds ratio (AOR) with the corresponding 95% confidence interval were computed. Variables with a p-value of <0.05 were considered statistically significant predictors of the outcome variable. Results: The incidence of postoperative pulmonary complication was 24.5%. Emergency procedures, preoperative SpO2 <94%, duration of surgery >2hr, patients with a nasogastric tube, intraoperative blood loss >500ml and post-operative albumin <3.5g/dl were factors associated with pulmonary complications. The most common complications were pneumonia (9.9%) followed by respiratory infection (4.2%). Conclusion: The incidence of postoperative pulmonary complication after thoracic and upper abdominal surgery remains high. Preoperative SpO2, duration of surgery, patients having a nasogastric tube, intraoperative blood loss and post-operative albumin were factors associated with post-operative pulmonary complications.